Effect of thermal annealing on the mechanical and thermal properties of polylactic acid–cellulosic fiber biocomposites. Issue 31 (28th April 2016) - Pérez‐Fonseca, A. A.; Robledo‐Ortíz, J. R.; González‐Núñez, R.; Rodrigue, D.
ABSTRACT: Polylactic acid (PLA) biocomposites were produced by a combination of extrusion and injection molding with three cellulosic reinforcements (agave, coir, and pine) and contents (10, 20, and 30%). In particular, some samples were subjected to thermal annealing (105 °C for 1 h) to modify the crystallinity of the materials. In all cases, morphological (scanning electron microscopy) and thermal (differential scanning calorimetry, dynamical mechanical thermal analysis) characterizations were related to the mechanical properties (Charpy impact, tensile and flexural tests). The results showed that annealing increased the crystallinity for all the materials produced, but different mechanical behaviors were observed depending on fiber type and content. For example, annealing increased the impact strength and flexural modulus of PLA and PLA biocomposites (agave, coir, and pine), while decreasing their flexural strength. But the main conclusion is that fiber addition combined with thermal annealing can substantially increase the thermal stability of the studied materials. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43750. Abstract :